2011
DOI: 10.1111/j.1365-2214.2011.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Child coping, parent coping assistance, and post‐traumatic stress following paediatric physical injury

Abstract: Findings suggest that children's coping strategies (particularly social withdrawal and resignation) play a possibly important, complex role in the development of traumatic stress symptoms. When parents help their child cope, children are more likely to seek out social support, suggesting that they will be more able to ask their parents for help as needed. Future research should identify effective strategies to prevent PTSS including how parents can best support their child following paediatric injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
43
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 33 publications
9
43
0
5
Order By: Relevance
“…endorsing avoidance of trauma cues) and general overprotective support style, were associated with both a standard measure of parental overprotection and higher child PTSS. The association between maladaptive parenting style and child PTSS is consistent with preliminary empirical evidence that parents’ own coping and response can influence a child’s post-trauma coping (Cobham, McDermott, Haslam, & Sanders, 2016; Marsac et al, 2013) and psychological adjustment (Ostrowski, Christopher, & Delahanty, 2006). Such parenting behaviours may increase a child’s perceived vulnerability to threat post-trauma and prevent the elaboration and processing of the child’s trauma memory (Salmond et al, 2011; Wood et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…endorsing avoidance of trauma cues) and general overprotective support style, were associated with both a standard measure of parental overprotection and higher child PTSS. The association between maladaptive parenting style and child PTSS is consistent with preliminary empirical evidence that parents’ own coping and response can influence a child’s post-trauma coping (Cobham, McDermott, Haslam, & Sanders, 2016; Marsac et al, 2013) and psychological adjustment (Ostrowski, Christopher, & Delahanty, 2006). Such parenting behaviours may increase a child’s perceived vulnerability to threat post-trauma and prevent the elaboration and processing of the child’s trauma memory (Salmond et al, 2011; Wood et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…One factor identified as a robust predictor of a child’s post-trauma psychological outcomes is their perceived social support (Kolaitis, 2017; Maercker & Hecker, 2016; Trickey, Siddaway, Meiser-Stedman, Serpell, & Field, 2012). Following a child’s experience of trauma, parents are often the primary source of support (Marsac, Donlon, Winston, & Kassam-Adams, 2013) and meta-analytic findings have confirmed that parenting style has a small yet significant impact on a child’s post-trauma mental health (Williamson, Creswell, Fearon et al, 2017). However, the extant literature has largely focused on general parenting responses, such as general overprotection, with little focus on parenting that may be trauma-specific, reflecting the lack of empirically validated, trauma-specific parenting measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda em relação às estratégias de enfrentamento, alguns estudos têm demonstrado uma maior variabilidade de uso de estratégias de enfrentamento entre crianças que passam por algum po de adoecimento (Marsac, Donlon, Winston, & Kassam-Adams, 2013). Além disso, segundo esses autores, a necessidade de exposição a procedimentos médicos invasivos exige que essas crianças acionem recursos pessoais e também externos para lidar com a adversidade (Marsac et al, 2013 , 2012).…”
Section: Introductionunclassified
“…Além disso, segundo esses autores, a necessidade de exposição a procedimentos médicos invasivos exige que essas crianças acionem recursos pessoais e também externos para lidar com a adversidade (Marsac et al, 2013 , 2012). Nesse contexto, buscou-se, no presente estudo, descrever, comparar e analisar estraté-gias de enfrentamento e o mismo em crianças com câncer e crianças sem câncer.…”
Section: Introductionunclassified